2023
DOI: 10.3390/cancers15020360
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Thymic Epithelial Tumors

Abstract: Thymic epithelial tumors (TETs) arise from the epithelial cells of the thymus and consist in the 1% of all adult malignancies, despite the fact that they are the most common lesions of the anterior mediastinum. TETs can be divided mainly into thymomas, thymic carcinomas, and the rarest ad aggressive neuroendocrine forms. Despite the surgical resection is quite resolving, the diagnosis of TETs is complicated by the absence of symptoms and the clinical presentation aggravated by several paraneoplastic disorders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 185 publications
0
9
0
Order By: Relevance
“…Increased DNMT activity in cancer cells is associated with tumor aggressiveness and poor patient prognosis [ 60 ]. Numerous published studies, summarized in recent reviews [ 61 , 62 ], have addressed the epigenetics of TETs. Most of the available literature has focused on the potential use of DNA methylation markers to discriminate between different histologic subtypes or between THs with and without myasthenia gravis or as a prognostic indicator.…”
Section: Altered Dna Methylation and Acetylation In Thymomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased DNMT activity in cancer cells is associated with tumor aggressiveness and poor patient prognosis [ 60 ]. Numerous published studies, summarized in recent reviews [ 61 , 62 ], have addressed the epigenetics of TETs. Most of the available literature has focused on the potential use of DNA methylation markers to discriminate between different histologic subtypes or between THs with and without myasthenia gravis or as a prognostic indicator.…”
Section: Altered Dna Methylation and Acetylation In Thymomasmentioning
confidence: 99%
“…Studies analyzing global methylation patterns in TETs have found substantial hyper- or hypomethylation of CpG sites with significant correlations with the TH histologic subtype [ 4 , 63 , 64 , 65 ], GTF2I or HRAS mutation status, and mRNA and miRNA expression patterns [ 4 ]. Previous studies using a candidate gene approach revealed the hypomethylation of several tumor suppressor genes (e.g., APC1A , CDKN2A , E-cad , FHIT , hMLH1 , MGMT , RARβ , RASSF1A ) or hypermethylation of DNMT1 , DNMT3a , and DNMT3b [ 66 ] in early stage THs compared to more aggressive or late stage THs and TCs (reviewed in [ 61 , 62 ]). The specific silencing of these genes with a role in regulating cell cycle progression and DNA repair suggests an essential step during TH progression.…”
Section: Altered Dna Methylation and Acetylation In Thymomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic modifications, such as DNA methylation changes, aberrant expression of non-coding RNAs, and post-translational modifications of histone tails, have emerged as pivotal drivers of genomic instability and chromosomal aberrations in cancer cells ( Figure 2 ). These modifications intricately modulate the gene expression landscape, activating transposable elements, upregulating oncogenes, and silencing tumor suppressor genes, thereby fostering the onset and progression of tumorigenesis ( 76 ). Remarkably, a subset of epigenetic genes implicated in chromatin remodeling (e.g., SMARCA4), histone modifications (e.g., BAP1, SETD2, ASXL1), and DNA methylation (e.g., TET2, DNMT3A, WT1) exhibits recurrent somatic mutations.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Depending on their enzymatic activities and substrate specificities, they are classified into four classes, and their inhibition leads to a more open chromatin, allowing the access of transcription factors to regulatory sites, facilitating the activation of gene expression [18]. So far, studies have provided indirect evidence regarding the involvement of histone post-translational modifications, including deacetylation, in the pathogenesis of TETs (reviewed in [19]). Low HDAC6 expression has been correlated with a dismal prognosis of patients with TETs based on the pan-cancer analysis of TCGA, genotype-tissue expression (GTEx), and the Cancer Cell Line Encyclopedia (CCLE) datasets [20].…”
Section: Introductionmentioning
confidence: 99%